2020
DOI: 10.1002/apj.2487
|View full text |Cite
|
Sign up to set email alerts
|

Chemical components analysis of Toona sinensis bark and wood by pyrolisis–gas chromatography–mass spectrometry

Abstract: The production of energy from wood biomass is as old as humanity itself. There has been enormous progress in research of sustainable pyrolysis processes for optimal energy conversion in the past 30 years. Pyrolisis–gas chromatography–mass spectrometry (PY‐GC‐MS) was used to examine the components of bark and wood of Toona sinensis for expanding high value utilization different parts of trees. In the study, 174 chemical constituents were identified in the bark; 169 chemical constituents were identified in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A recent study showed that terpenoids, phenylpropanoids, and flavonoids, known as bioactive substances derived from the extracts of T. sinensis leaves and bark have been identified to have anti-tumor, antioxidant, anti-inflammatory, antibacterial, antiviral, hepatoprotective, and hypoglycemic effects (Ji et al, 2021). T. sinensis in Taihe, Anhui has many varieties such as 'Heiyouchun', the most famous variety because of its taste, aroma, and nutritional value that was offered as a tribute as early as the Tang Dynasty (Yang et al, 2020a). In the early stage when the solar term of Grain Rain is coming, the 'Heiyouchun' shows the best quality, strong aroma, and good taste because its sprouts are thick, fat, and tender with the best oils, strong fragrances, and crunchiness (Sui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that terpenoids, phenylpropanoids, and flavonoids, known as bioactive substances derived from the extracts of T. sinensis leaves and bark have been identified to have anti-tumor, antioxidant, anti-inflammatory, antibacterial, antiviral, hepatoprotective, and hypoglycemic effects (Ji et al, 2021). T. sinensis in Taihe, Anhui has many varieties such as 'Heiyouchun', the most famous variety because of its taste, aroma, and nutritional value that was offered as a tribute as early as the Tang Dynasty (Yang et al, 2020a). In the early stage when the solar term of Grain Rain is coming, the 'Heiyouchun' shows the best quality, strong aroma, and good taste because its sprouts are thick, fat, and tender with the best oils, strong fragrances, and crunchiness (Sui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…T. sinensis is divided into two types based on the color of tender leaves and petioles: red T. sinensis and green T. sinensis [13,14]. Red T. sinensis is rich in anthocyanins, thus the leaves and petioles are purple [15].…”
Section: Introductionmentioning
confidence: 99%